Composite material, preparation method and electronic equipment
By introducing a transition layer with a melting point lower than the base layer and the hardened layer into the layered composite material, the problem of insufficient interface bonding strength between material layers with large composition differences is solved, and the improvement of high interface bonding strength and material density is achieved.
Patent Information
- Application Number
- CN202311149371.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-06
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2043-09-06
AI Technical Summary
Among the existing layered composite materials, it is difficult to obtain higher interfacial bonding strength between material layers with large composition differences, which limits the selection of material layer components.
By introducing a transition layer, the melting point of the transition layer material is lower than the melting point of the substrate layer and the hardened layer material. The transition layer melts during the sintering process and flows into the base layer and hardened layer to improve the interface bonding strength.
The high interfacial bonding strength between material layers with large composition differences is achieved, the density and structural stability of the material are improved, and the interface bonding strength reaches more than 400MPa.
Smart Images

Figure CN119567652A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of composite materials, and in particular to a composite material, a manufacturing method and an electronic device. Background Art
[0002] For layered composite materials, in order to ensure the bonding strength of two layers of materials, the components of the two layers of materials need to be close, otherwise the material is prone to cracking and deformation. Therefore, in existing layered composite materials, high interface bonding strength cannot be obtained between material layers with large composition differences, and the selection of the components of each material layer has great limitations. Summary of the invention
[0003] In view of this, the present application provides a composite material, a preparation method and an electronic device to achieve a higher interface bonding strength between material layers with greatly different compositions.
[0004] In a first aspect, an embodiment of the present application provides a composite material, which includes a base layer, a hardening layer and a transition layer, wherein the transition layer is arranged between the base layer and the hardening layer, and the melting point of the transition layer material is lower than the melting point of the base layer material and the melting point of the hardening layer material.
[0005] The composite material provided in the present application can improve the element distribution at the interface of the base layer and the hardened layer by introducing a transition layer, which is beneficial to improving the interface bonding strength. At the same time, it also broadens the selection space of the base layer and the hardened layer materials. The transition layer can achieve the reliability of the bonding between two materials with large differences, improve the interface bonding strength, and enable the interface bonding strength to reach more than 400MPa.
[0006] In a possible design, the material of the transition layer is one of cobalt, copper, and nickel-iron alloy. These materials used in the transition layer can melt when the sintering temperature is reached, and change from a solid phase to a liquid phase, so that they can flow and penetrate between the solid phase matrix layer and the hardened layer material particles, and the capillary force of the liquid phase can condense the powder particles and improve the bonding force.
[0007] In a possible design, the thickness of the transition layer is 10% to 20% of the thickness of the composite material. By making the thickness of the transition layer within this ratio, a suitable liquid phase effect can be ensured and the density of the composite material can be improved.
[0008] In a possible design, the material of the base layer is stainless steel. The melting point of the stainless steel used in the base layer is greater than the sintering temperature, that is, when the sintering temperature reaches 1000°C to 1200°C, the base layer made of stainless steel will not be melted, so that the material particles of the base layer can still remain in the solid phase, and the solid phase particles are sintered and combined through mechanisms such as diffusion, local evaporation and condensation, and gradually become dense.
[0009] In a possible design, the thickness of the base layer is 50% to 70% of the thickness of the composite material. By making the thickness of the base layer within this ratio, the composite material can be guaranteed to have appropriate toughness, and at the same time, the composite material can be guaranteed to have high structural strength and structural stability, so that the composite material can have a long service life.
[0010] In a possible design, the material of the hardened layer is one of FeCoNiCrAl, FeCoNiCuAl, and FeCoNiCuMo. The hardened layer made of such material can have a relatively high hardness, which can reach above 45HRC.
[0011] In a possible design, the thickness of the hardened layer is 20% to 40% of the thickness of the composite material. By making the thickness of the hardened layer within this ratio, the surface hardness of the hardened layer can be ensured while ensuring the bonding strength, so that the composite material can maintain a stable shape when used in the product.
[0012] In a possible design, the thickness of the composite material is between 4 mm and 8 mm, so that the composite material can be made thinner and lighter while ensuring that different materials have a high interface bonding strength.
[0013] In a second aspect, the present application further provides a method for preparing the composite material provided in the first aspect of the present application, wherein the method comprises the following steps:
[0014] The base layer powder, the transition layer powder and the hardening layer powder are respectively mixed with a binder through a granulation process to obtain a base layer feed, a transition layer feed and a hardening layer feed;
[0015] Injecting the base layer feed material, the transition layer feed material and the hardening layer feed material into the mold cavity in sequence to obtain a green body;
[0016] performing cold isostatic pressing on the green body;
[0017] Removing the binder in the green body through a degreasing process to obtain a degreasing body;
[0018] Performing a sintering densification treatment on the debinded blank;
[0019] The debinded blank which has been subjected to sintering and densification treatment is subjected to deep cryogenic treatment to obtain a composite material.
[0020] Among them, the composite material prepared by this preparation process has the same technical effect as the above composite material, which will not be described in detail here.
[0021] In a possible design, the average particle size of the transition layer powder is between 10 μm and 20 μm. By optimizing the thickness of the transition layer and the particle size of the transition layer powder at the same time, the liquid phase material of the transition layer can have better wettability with the solid phase particles of the base layer and the hardened layer, which is conducive to bringing the two solid phase particles closer to each other through the capillary suction of the liquid phase material, thereby improving the density.
[0022] In a possible design, the average particle size of the base layer powder is between 5 μm and 10 μm, which is conducive to achieving high density of the composite material while reducing the preparation cost of various material powders.
[0023] In a possible design, the average particle size of the hardened layer powder is between 5 μm and 15 μm, which is conducive to achieving high density of the composite material while reducing the preparation cost of various material powders.
[0024] In a possible design, the molding pressure of the cold isostatic pressing is between 50 MPa and 200 MPa, and the holding time is between 0.5 h and 1 h, thereby ensuring that the green body has a higher density while saving production costs.
[0025] In one possible design, the sintering densification process adopts a hot isostatic pressing sintering process, with a sintering temperature between 1000°C and 1200°C, a holding time between 1h and 4h, and a holding pressure between 100MPa and 300MPa, thereby ensuring that the sintered material has a higher density and ideal material properties.
[0026] In a possible design, the binder includes, by mass percentage, 75% to 85% polyoxymethylene, 5% to 15% polyethylene, and 5% to 15% stearic acid. The binder with such a material ratio can make the aforementioned various feed materials have ideal fluidity, which is conducive to improving the molding effect of the green body in the subsequent process.
[0027] In a possible design, in the base layer feed, the volume ratio of the base layer powder to the binder is between (55%-60%): (45%-40%); the volume ratio of the transition layer powder to the binder is between (50%-55%): (50%-45%); the volume ratio of the hardening layer powder to the binder is between (60%-65%): (40%-35%). Thus, the performance of various feeds can be guaranteed while reducing production costs.
[0028] In a possible design, the removing the binder in the green body by a degreasing process specifically includes:
[0029] Heat to 300°C to 400°C at a rate of 3°C / min to 8°C / min, and keep warm for 1h to 4h;
[0030] Heat to 700℃~800℃ at a rate of 5℃ / min~10℃ / min, and keep warm for 3h~6h;
[0031] Allow to cool to room temperature.
[0032] Among them, a two-stage heating step is adopted to reach the target debinding temperature to remove the binder, and the corresponding heating rate and holding time are controlled, so as to effectively control the debinding rate, make the binder almost completely removed, and avoid defects such as uneven carbon content distribution, deformation, and cracks in the green body during the debinding process.
[0033] In a possible design, the process temperature of the mixing and granulating process is between 140°C and 190°C, the mixing and granulating time is between 1h and 6h, and the rotation speed of the mixing and granulating equipment is between 70r / min and 130r / min, thereby ensuring the feeding performance and helping to reduce costs.
[0034] In one possible design, in the step of sequentially injecting the base layer feed, transition layer feed and hardening layer feed into the mold cavity, the injection temperature is between 150°C and 185°C, the injection pressure is between 60MPa and 120MPa, and the mold cavity temperature is between 40°C and 110°C, thereby obtaining a green body with a relatively stable structure and preventing the problem of uneven green body density caused by injection.
[0035] In a third aspect, the present application further provides an electronic device, which includes the composite material provided in the first aspect of the present application. The electronic device including the composite material has similar technical effects as the composite material, which will not be described in detail here.
[0036] It should be understood that the foregoing general description and the following detailed description are exemplary only and are not restrictive of the present application. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.
[0038] Figure 1 A schematic diagram of the structure of the composite material provided in the embodiment of the present application;
[0039] Figure 2 A flow chart of the preparation method provided in the embodiments of the present application.
[0040] Description of reference numerals:
[0041] 1-base layer;
[0042] 2-hardening layer;
[0043] 3- Transition layer. DETAILED DESCRIPTION
[0044] In order to better understand the technical solution of the present application, the embodiments of the present application are described in detail below with reference to the accompanying drawings.
[0045] It should be clear that the described embodiments are only part of the embodiments of the present application, rather than all the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present application.
[0046] The terms used in the embodiments of the present application are only for the purpose of describing specific embodiments, and are not intended to limit the present application. The singular forms "a", "said" and "the" used in the embodiments of the present application and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.
[0047] It should be understood that the term "and / or" used in this article is only a description of the association relationship of associated objects, indicating that there can be three relationships. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in this article generally indicates that the associated objects before and after are in an "or" relationship.
[0048] In the description of this application, unless otherwise clearly specified and limited, the terms "first" and "second" are used for descriptive purposes only and cannot be understood as indicating or implying relative importance; unless otherwise specified or explained, the term "plurality" refers to two or more; the terms "connected" and "fixed" should be understood in a broad sense, for example, "connected" can be a fixed connection, a detachable connection, an integral connection, or an electrical connection; it can be directly connected or indirectly connected through an intermediate medium. For ordinary technicians in this field, the specific meanings of the above terms in this application can be understood according to specific circumstances.
[0049] For layered composite materials, in order to ensure the bonding strength of two adjacent layers of materials, the components of the two layers of materials need to be close, otherwise the problem of material cracking and deformation may occur easily. For example, one layer in the composite material adopts WC-Co hard alloy as the matrix material, and the other layer adopts WC-Co hard alloy with TiN, TiC, Al2O3 or multi-element alloy with TiC and TiN added as the coating material, and the main materials in the two layers of materials are WC-Co hard alloy, so that the bonding strength of the two layers of materials can be guaranteed. However, when one of the layers adopts other materials with large differences other than WC-Co hard alloy, the bonding strength of the two layers of materials will be significantly reduced, and the problem of cracking and deformation may occur easily. Therefore, in the existing layered composite materials, it is impossible to obtain a higher interface bonding strength between the material layers with large composition differences, which has a large limitation on the selection of the components of each material layer.
[0050] Figure 1 The schematic diagram of the structure of the composite material provided in the embodiment of the present application is shown in FIG. Figure 1 The present application embodiment provides a composite material, which can be used to prepare electronic devices, such as mobile phones, tablet computers, and vehicle-mounted products. The present embodiment does not limit the type of electronic devices. In addition, the composite material can also be used to prepare parts with surface wear resistance requirements such as rotating shaft parts in electronic devices.
[0051] The composite material comprises a base layer, a hardening layer and a transition layer, wherein the transition layer is arranged between the base layer and the hardening layer, and the melting point of the transition layer material is lower than the melting point of the base layer material and the melting point of the hardening layer material. In the preparation process of the composite material, material powders for preparing the base layer, the hardening layer and the transition layer, namely, base layer powder, hardening layer powder and transition layer powder, can be prepared first. The base layer powder, hardening layer powder and transition layer powder are respectively mixed with corresponding amounts of binders, and corresponding base layer feed, hardening layer feed and transition layer feed are obtained by mixing and granulating processes respectively. Then, the base layer feed, hardening layer feed and transition layer feed are sequentially injected into the mold cavity by co-injection molding technology to obtain a green body. Then, the obtained green body is subjected to cold isostatic pressing treatment. Then, the binder in the green body is removed by a degreasing process, and finally, a composite structural part is obtained by sintering, densification and deep cryogenic treatment.
[0052] Among them, in the sintering densification step, when heated to the sintering temperature, the melting point of the transition layer material is lower than the melting point of the base layer material and the melting point of the hardening layer material. The transition layer material will melt before the base layer material and the hardening layer material, and the transition layer material will be transformed from solid phase to liquid phase, while the base layer material and the hardening layer material will still remain in solid phase. The liquid phase transition layer material will flow and penetrate between the solid phase base layer material particles and the hardening layer material particles. There is good wettability between the liquid phase particles and the solid phase particles. With the flow of the liquid phase transition layer material, the liquid phase surface between the two solid phase particles bends toward the liquid phase side, thereby generating a capillary suction. Under the action of this suction, the two solid phase particles can be brought closer to each other, and finally the densification of the sintered body is achieved. The density of the composite material obtained can reach more than 98%. By introducing the transition layer, it can act as a bridge between the interface of the base layer and the hardened layer, improve the element distribution at the interface of the base layer and the hardened layer, and help improve the interface bonding strength. At the same time, it also broadens the selection space of the base layer and the hardened layer materials. The transition layer can achieve the reliability of the bonding between two materials with large differences, improve the interface bonding strength, and make the interface bonding strength reach more than 400MPa.
[0053] In one embodiment, the material of the transition layer can be one of cobalt Co, copper Cu, and nickel-iron alloy Ni-Fe. In the aforementioned sintering step, the sintering temperature can be 1000°C to 1200°C. When the sintering temperature is reached, these materials used in the transition layer can melt and change from a solid phase to a liquid phase, so that they can flow and penetrate between the solid phase matrix layer and the hardening layer material particles. The capillary force of the liquid phase can condense the powder particles and improve the bonding force.
[0054] In one embodiment, the material of the base layer may be stainless steel, and optionally, the grade of the stainless steel used in the base layer may be one of 304L, 316L, and HK30. The melting point of the stainless steel used in the base layer is greater than the sintering temperature, that is, when the sintering temperature reaches 1000°C to 1200°C, the base layer made of stainless steel will not be melted, so that the material particles of the base layer can still remain in the solid phase, and the solid phase particles are sintered and combined through mechanisms such as diffusion, local evaporation and condensation, and gradually become dense.
[0055] In one embodiment, the material of the hardened layer can be one of FeCoNiCrAl, FeCoNiCuAl, and FeCoNiCuMo. The material powder of the hardened layer is a mixture of five metal powders in an equimolar ratio, and the purity of the five metal element powders is not less than 99.9%. Exemplarily, when the material of the hardened layer is FeCoNiCrAl, the material powder of the hardened layer is a mixture of iron Fe, cobalt Co, nickel Ni, chromium Cr, and aluminum Al. Exemplarily, when the material of the hardened layer is FeCoNiCuAl, the material powder of the hardened layer is a mixture of iron Fe, cobalt Co, nickel Ni, copper Cu, and aluminum Al. Exemplarily, when the material of the hardened layer is FeCoNiCuMo, the material powder of the hardened layer is a mixture of iron Fe, cobalt Co, nickel Ni, copper Cu, and molybdenum Mo. The hardened layer composed of such materials can have a higher hardness, and the hardness can reach above 45HRC.
[0056] In one embodiment, the thickness of the transition layer is 10% to 20% of the thickness of the composite material. By making the thickness of the transition layer within this ratio, a suitable liquid phase effect can be ensured and the density of the composite material can be improved.
[0057] In one embodiment, the thickness of the base layer is 50% to 70% of the thickness of the composite material. By making the thickness of the base layer within this ratio, the composite material can be guaranteed to have appropriate toughness, and at the same time, the composite material can be guaranteed to have high structural strength and structural stability, so that the composite material can have a long service life.
[0058] In one embodiment, the thickness of the hardened layer is 20% to 40% of the thickness of the composite material. By making the thickness of the hardened layer within this ratio, the surface hardness of the hardened layer can be ensured while ensuring the bonding strength, so that the composite material can maintain a stable shape when used in the product.
[0059] In one embodiment, the thickness of the composite material is between 4 mm and 8 mm, which can achieve a thinner composite material while ensuring that different materials have a high interface bonding strength. In one embodiment, the thickness of the transition layer is between 0.4 mm and 1.6 mm.
[0060] Figure 2 The flowchart of the preparation method provided in the embodiment of the present application is shown in FIG. Figure 2 The present application also provides a method for preparing the composite material, wherein the method comprises the following steps:
[0061] Step S1, mixing the base layer powder, transition layer powder and hardening layer powder with a binder through a mixing and granulation process to obtain a base layer feed, a transition layer feed and a hardening layer feed.
[0062] Before step S1, the base layer powder, transition layer powder and hardening layer powder may be prepared respectively. Then, the base layer powder, transition layer powder and hardening layer powder may be mixed with corresponding amounts of binder, and the base layer feed material, transition layer feed material and hardening layer feed material may be prepared respectively through mixing and granulation processes.
[0063] Among them, the average particle size of the transition layer powder is between 10μm and 20μm, and at the same time, the thickness of the transition layer can be controlled to be 10% to 20% of the thickness of the composite material. Therefore, by optimizing the thickness of the transition layer and the particle size of the transition layer powder at the same time, the liquid phase material of the transition layer can have better wettability with the solid phase particles of the matrix layer and the hardening layer, which is conducive to bringing the two solid phase particles closer to each other through the capillary suction of the liquid phase material and improving the density. In addition, the average particle size of the matrix layer powder is between 5μm and 10μm, and the average particle size of the hardening layer powder is between 5μm and 15μm, which is also conducive to achieving high density of the composite material and reducing the preparation cost of various material powders.
[0064] In one embodiment, the mixing and granulating process can be carried out by mixing and granulating equipment, the process temperature can be between 140°C and 190°C, the mixing and granulating time can be between 1h and 6h, and the rotation speed of the mixing and granulating equipment can be between 70r / min and 130r / min, thereby ensuring the feeding performance and helping to reduce costs.
[0065] In one embodiment, the binder includes, by mass percentage, 75% to 85% polyoxymethylene, 5% to 15% polyethylene, and 5% to 15% stearic acid. The ratio ranges of the various materials all include the endpoint values. The binder with such a material ratio can make the aforementioned various feed materials have ideal fluidity, which is beneficial to improving the molding effect of the green body in the subsequent process.
[0066] In one embodiment, the binder comprises, by mass percentage, 80% polyoxymethylene, 10% polyethylene, and 10% stearic acid.
[0067] In one embodiment, the binder includes, by mass percentage, 78% polyoxymethylene, 13% polyethylene, and 9% stearic acid.
[0068] In one embodiment, the binder includes, by mass percentage, 82% polyoxymethylene, 7% polyethylene, and 11% stearic acid.
[0069] The material ratio of the binder in the above-mentioned various embodiments can make the above-mentioned various feed materials have ideal fluidity, which is beneficial to improving the forming effect of the green body in the subsequent process.
[0070] In one embodiment, as described above, the base layer powder in step S1 is mixed with a corresponding amount of binder to prepare the base layer feed, the transition layer powder is mixed with a corresponding amount of binder to prepare the transition layer feed, and the hardening layer powder is mixed with a corresponding amount of binder to prepare the hardening layer feed. In order to ensure the performance of various feeds and reduce production costs, the volume ratio of the base layer powder to the binder is between (55% to 60%): (45% to 40%), the volume ratio of the transition layer powder to the binder is between (50% to 55%): (50% to 45%), and the volume ratio of the hardening layer powder to the binder is between (60% to 65%): (40% to 35%). The numerical ranges of the above-mentioned volume ratios all include endpoint values.
[0071] In one embodiment, the volume ratio of the base layer powder to the binder is 56%:44%, the volume ratio of the hardening layer powder to the binder is 62%:38%, and the volume ratio of the transition layer powder to the binder is 52%:48%.
[0072] In one embodiment, the volume ratio of the base layer powder to the binder is 58%:42%, the volume ratio of the hardening layer powder to the binder is 64%:36%, and the volume ratio of the transition layer powder to the binder is 53%:47%.
[0073] Step S2: injecting the base layer feed, the transition layer feed and the hardening layer feed into the mold cavity in sequence to obtain a green body.
[0074] Among them, the base layer feed, transition layer feed and hardening layer feed can be injected into the mold cavity in sequence by using the co-injection molding technology. In this process, the injection temperature is between 150℃ and 185℃, the injection pressure is between 60MPa and 120MPa, and the mold cavity temperature is between 40℃ and 110℃, thereby obtaining a green body with a relatively stable structure, which can prevent the problem of uneven green body density caused by injection. Among them, the base layer, transition layer and hardening layer in the green body can be arranged in sequence.
[0075] Step S3, performing cold isostatic pressing on the green body.
[0076] Among them, by cold isostatic pressing the green body, the density of the green body can be increased and the porosity can be reduced, which can lay the foundation for achieving high density through the subsequent sintering process. In one embodiment, the molding pressure of the cold isostatic pressing is between 50MPa and 200MPa, and the holding time is between 0.5h and 1h, thereby ensuring that the green body has a higher density and saving production costs.
[0077] Step S4: removing the binder in the green body through a degreasing process to obtain a degreasing body.
[0078] Among them, the green body obtained after cold isostatic pressing has a certain interface bonding strength, and after removing the binder, it can still maintain stable structural characteristics, and a degreased body including only base layer material, transition layer material and hardened layer material can be obtained.
[0079] In one embodiment, the debinding process may specifically be a thermal debinding process. In the process of removing the binder in the green body by the debinding process, the following steps may be specifically adopted:
[0080] Step S41, first heat to 300°C to 400°C at a speed of 3°C / min to 8°C / min, and keep warm for 1h to 4h.
[0081] Step S42, heating to 700°C-800°C at a speed of 5°C / min-10°C / min, and keeping the temperature for 3h-6h.
[0082] Step S43, cooling to room temperature. In one embodiment, the furnace may be naturally cooled to room temperature.
[0083] Among them, thermal debinding is used, and a two-stage heating step of step S41 and step S42 is adopted to reach the target debinding temperature to remove the binder, and the corresponding heating rate and holding time are controlled, so as to effectively control the debinding rate, so that the binder is almost completely removed, and the defects such as uneven carbon content distribution, deformation, and cracks in the green body during the debinding process are avoided.
[0084] Step S5, sintering and densifying the degreased blank.
[0085] Among them, the sintering densification treatment can adopt the hot isostatic pressing sintering process. During the operation, the debinded blank can be placed in a closed container, the container is evacuated, and the vacuum degree is controlled to be less than or equal to 5×10 -3 Pa, and then high-pressure argon is input into the container through a compressor, and at the same time, it is heated by a heating furnace in the container, so that the degreased blank can be densified under the action of high temperature and high pressure. Among them, the same pressure acts evenly on the surface of the degreased blank from all directions, so that the internal structure of the material of the degreased blank is uniform. Through this sintering method, the rapid densification of the powder can be better promoted through a larger driving force. At the same time, due to the short insulation time, the growth of grains can be well avoided, thereby effectively improving the performance of the product formed by the composite material. In addition, the above-mentioned hot isostatic pressing sintering process has the characteristics of uniform heating, low sintering temperature, short sintering time, small and uniform grain size, etc., which can greatly improve production efficiency and is easy to achieve mass production.
[0086] In one embodiment, the sintering densification treatment process adopts a hot isostatic pressing sintering process, the sintering temperature is between 1000°C and 1200°C, the holding time is between 1h and 4h, and the holding pressure is between 100MPa and 300MPa, thereby ensuring that the sintered material has a higher density and ideal material properties.
[0087] Step S6, performing deep cryogenic treatment on the debinded blank after sintering and densification treatment to obtain a composite material.
[0088] Among them, liquid nitrogen and other media can be used to perform cryogenic treatment on the degreased blank after sintering and densification treatment, and the insulation time of cryogenic treatment is between 5h and 10h. Cryogenic treatment can be used to reduce the residual thermal stress in the composite material. This thermal stress refers to a kind of stress generated by the temperature difference during the sintering process of the product. The source of thermal stress includes the temperature difference between the furnace chamber and the environment during the heating and cooling process. Excessive accumulation of thermal stress will affect the bonding strength between the materials and even cause cracking and deformation of the product. Using the cryogenic treatment process, when the ambient temperature drops significantly, the volume of the material will shrink, and the compressive stress on the surrounding area will decrease, which can greatly reduce the residual stress and achieve the purpose of improving product performance.
[0089] The above are only preferred embodiments of the present application and are not intended to limit the present application. For those skilled in the art, the present application may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.
Claims
1. A composite material, characterized in that: include: Base layer; Hardened layer; A transition layer is provided between the base layer and the hardening layer, and the melting point of the material of the transition layer is lower than the melting point of the material of the base layer and the melting point of the material of the hardening layer.
2. The composite material according to claim 1, characterized in that The material of the transition layer is one of cobalt, copper and nickel-iron alloy.
3. The composite material according to claim 1 or 2, characterized in that: The thickness of the transition layer is 10% to 20% of the thickness of the composite material.
4. The composite material according to any one of claims 1 to 3, characterized in that The material of the base layer is stainless steel.
5. The composite material according to any one of claims 1 to 4, characterized in that: The thickness of the base layer is 50% to 70% of the thickness of the composite material.
6. The composite material according to any one of claims 1 to 5, characterized in that: The material of the hardened layer is one of FeCoNiCrAl, FeCoNiCuAl and FeCoNiCuMo.
7. The composite material according to any one of claims 1 to 6, characterized in that: The thickness of the hardened layer is 20% to 40% of the thickness of the composite material.
8. The composite material according to any one of claims 1 to 7, characterized in that: The thickness of the composite material is between 4 mm and 8 mm.
9. A method for preparing the composite material according to any one of claims 1 to 8, characterized in that: The steps include: The base layer powder, the transition layer powder and the hardening layer powder are respectively mixed with a binder through a granulation process to obtain a base layer feed, a transition layer feed and a hardening layer feed; Injecting the base layer feed material, the transition layer feed material and the hardening layer feed material into the mold cavity in sequence to obtain a green body; performing cold isostatic pressing on the green body; Removing the binder in the green body through a degreasing process to obtain a degreasing body; Performing a sintering densification treatment on the debinded blank; The debinded blank which has been subjected to sintering and densification treatment is subjected to deep cryogenic treatment to obtain a composite material.
10. The preparation method according to claim 9, characterized in that: The average particle size of the transition layer powder is between 10 μm and 20 μm.
11. The preparation method according to claim 9 or 10, characterized in that: The average particle size of the base layer powder is between 5 μm and 10 μm.
12. The preparation method according to any one of claims 9 to 11, characterized in that: The average particle size of the hardened layer powder is between 5 μm and 15 μm.
13. The preparation method according to any one of claims 9 to 12, characterized in that: The molding pressure of the cold isostatic pressing is between 50MPa and 200MPa, and the holding time is between 0.5h and 1h.
14. The preparation method according to any one of claims 9 to 13, characterized in that: The sintering densification treatment process adopts a hot isostatic pressing sintering process, the sintering temperature is between 1000° C. and 1200° C., the holding time is between 1 h and 4 h, and the holding pressure is between 100 MPa and 300 MPa.
15. The preparation method according to any one of claims 9 to 14, characterized in that: The binder comprises, by mass percentage, 75% to 85% of polyoxymethylene, 5% to 15% of polyethylene, and 5% to 15% of stearic acid.
16. The preparation method according to any one of claims 9 to 15, characterized in that: In the matrix layer feeding, the volume ratio of the matrix layer powder to the binder is between (55% to 60%): (45% to 40%); The volume ratio of the transition layer powder to the binder is between (50% to 55%) and (50% to 45%); The volume ratio of the hardened layer powder to the binder is between (60% to 65%): (40% to 35%).
17. The preparation method according to any one of claims 9 to 16, characterized in that: The removing of the binder in the green body by a degreasing process specifically comprises: Heat to 300°C to 400°C at a rate of 3°C / min to 8°C / min, and keep warm for 1h to 4h; Heat to 700℃~800℃ at a rate of 5℃ / min~10℃ / min, and keep warm for 3h~6h; Allow to cool to room temperature.
18. The preparation method according to any one of claims 9 to 17, characterized in that: The process temperature of the mixing and granulating process is between 140° C. and 190° C., the mixing and granulating time is between 1 hour and 6 hours, and the rotation speed of the mixing and granulating equipment is between 70 r / min and 130 r / min.
19. The preparation method according to any one of claims 9 to 18, characterized in that: In the step of sequentially injecting the base layer feed, transition layer feed and hardening layer feed into the mold cavity, the injection temperature is between 150°C and 185°C, the injection pressure is between 60MPa and 120MPa, and the mold cavity temperature is between 40°C and 110°C.
20. An electronic device, characterized in that: The composite material comprises the composite material according to any one of claims 1 to 8.
Citation Information
Patent Citations
Tungsten-transition layer / stainless steel hot isostatic pressing diffusion bonding method
CN109396631A
Austenitic stainless steel and hard alloy composite material and preparation method and application thereof
CN112008083A
Powder metallurgy preparation method for step-by-step formed cemented carbide hard alloy / steel double-layer structure composite material
CN112961998A
High-toughness corrosion-resistant FeCoNiCuAl high-entropy alloy wave-absorbing material as well as preparation method and application thereof
CN113621843A
Preparation method of high-performance metal-ceramic composite material
CN114101678A